ABOUT CONSTRUCTION OF ANALYTICAL APPROXIMATIONS OF ELEMENTS OF AN GRAVITY ANOMALOUS - YAKYMCHYK, A.; CHORNA, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The method of linear analytical approximations construction in gravimetry and magnetometry is shortly set out. The necessity of collaboration with organizations which are owned computers of powerful facilities for solution of the systems of the linear algebraic equations of the big dimension is offered.